2023
DOI: 10.3390/polym15122638
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib-Based Drug Delivery Systems: Applications and Perspectives

Abstract: As a Food and Drug Administration (FDA)-approved molecular-targeted chemotherapeutic drug, sorafenib (SF) can inhibit angiogenesis and tumor cell proliferation, leading to improved patient overall survival of hepatocellular carcinoma (HCC). In addition, SF is an oral multikinase inhibitor as a single-agent therapy in renal cell carcinoma. However, the poor aqueous solubility, low bioavailability, unfavorable pharmacokinetic properties and undesirable side effects (anorexia, gastrointestinal bleeding, and sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 93 publications
0
2
0
Order By: Relevance
“…Such SF nanomedicine systems have been evaluated in co-delivery with biomaterials, chemotherapeutic drugs, imaging agents, and active agents for receptor-mediated binding. They have also expressed great potential in application against various solid tumors, as has been recently reviewed by Wang et al [ 98 ].…”
Section: Nanomedicines For Targeting Tme: Application Of Natural and ...mentioning
confidence: 99%
“…Such SF nanomedicine systems have been evaluated in co-delivery with biomaterials, chemotherapeutic drugs, imaging agents, and active agents for receptor-mediated binding. They have also expressed great potential in application against various solid tumors, as has been recently reviewed by Wang et al [ 98 ].…”
Section: Nanomedicines For Targeting Tme: Application Of Natural and ...mentioning
confidence: 99%
“…According to a study, sorafenib appears to have an apparent volume of distribution of 213L. 7 In vitro testing has shown that sorafenib binds to plasma proteins at a rate of 99.5%. The liver plays a significant role in the metabolism of sorafenib, primarily through cytochrome P450 3A4 (CYP3A4) and glucuronidation via uridine diphosphate glucuronyltransferase 1A9 (UGT1A9).…”
Section: Introductionmentioning
confidence: 99%